Optimizing NotebookLM for Islamic Religious Education in the Age of Artificial Intelligence - Teguh Iman Santoso (PT. Berkah Digital Teknologi, 2026)
The rapid advancement of Artificial Intelligence (AI) is reshaping education, including Islamic Religious Education (PAI). However, the integration of AI into PAI instruction at STAI Sirojul Falah Bogor remains limited, as teaching practices still rely heavily on conventional methods and participants face challenges related to limited learning resources, digital literacy, and interactive instructional design. This community service activity aimed to optimize the use of NotebookLM as a source-based AI tool to support more efficient, accessible, and contextual PAI learning. The activity was implemented through a hybrid online and offline workshop on Friday, April 17, 2026, at STAI Sirojul Falah Bogor, involving PAI lecturers, students, and members of the academic community. The method included material preparation, introduction to AI in education, NotebookLM feature demonstration, guided hands-on practice, AI-assisted PAI learning simulations, discussion, and reflective evaluation. The results showed that participants were able to use NotebookLM to upload PAI learning materials, generate AI-assisted summaries, develop study guide drafts, create source-based quiz questions, and formulate discussion prompts grounded in uploaded sources. The workshop also strengthened participants’ awareness of ethical AI use, particularly in relation to source verification, responsible interpretation of AI outputs, and the need to align AI-generated materials with Islamic educational values. These findings indicate that NotebookLM can support PAI learning by helping lecturers and students transform religious education materials into more structured, interactive, and source-based learning resources. This activity contributes to strengthening digital literacy and provides a practical model for integrating AI tools ethically and contextually within Islamic higher education.